2012
DOI: 10.1063/1.3686289
|View full text |Cite
|
Sign up to set email alerts
|

Size effect and cylinder test on several commercial explosives

Abstract: Abstract. Some size (diameter) effect and the Cylinder test results for Kinepak (ammonium nitrate/nitromethane), Semtex 1, Semtex H and urea nitrate are presented. Cylinder test data appears normal despite faster sound speeds in the copper wall. Most explosives come to steady state in the Cylinder test as expected, but Kinepak shows a steadily increasing wall velocity with distance down the cylinder. Some data on powder densities as a function of loading procedure are also given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…However, earlier modeling showed a precursor shock in the wall ahead of the detonating explosives but the system came to steady state [14]. Four urea nitrate and shotgun powder shots showed self-similar behavior although one Kinepak (AN 79/NM 21) shot out of two did not, possibly because of a defective tube [15].…”
Section: Introductionmentioning
confidence: 92%
“…However, earlier modeling showed a precursor shock in the wall ahead of the detonating explosives but the system came to steady state [14]. Four urea nitrate and shotgun powder shots showed self-similar behavior although one Kinepak (AN 79/NM 21) shot out of two did not, possibly because of a defective tube [15].…”
Section: Introductionmentioning
confidence: 92%
“…Even at Table 2. Average rate of velocity decay (j R UD j) and run-to-failure (RTF) distances of each charge with published critical diameter data for charges of similar composition [16][17][18].…”
Section: Anà Almentioning
confidence: 99%
“…Work done by Souers et al [18] demonstrated that a charge of ANNM with a similar composition to that of ANNM20 failed to yield a steady detonation at a diameter of 12.78 mm. Since ANNM20 was the most sensitive ANNM composition (along with ANNM25 which had an equivalent j R UD j), this should indicate that all the charges tested in this work failed to produce a steady detonation.…”
Section: Annmmentioning
confidence: 99%